What is the additional value of MRI of the foot to the hand in undifferentiated arthritis to predict rheumatoid arthritis development? - Y. J. Dakkak; D. M. Boeters; A. C. Boer; M. Reijnierse; A. H. M. van der Helm-van Mil (Arthritis Research & Therapy, 2019)
Abstract Background MRI-detected subclinical joint inflammation in the hand joints of patients with undifferentiated arthritis (UA) predicts progression to rheumatoid arthritis (RA). It is unknown if adding MRI of the foot increases predictive accuracy compared to the hand alone. Methods 1.5-T contrast-enhanced MRI of the unilateral foot (MTP-1-5) and hand (MCP-2-5 and wrist) was performed in 123 patients presenting with UA (not fulfilling the 2010 RA criteria) and scored for bone marrow edema (BME), synovitis and tenosynovitis. Symptom-free controls (n = 193) served as a reference for defining an abnormal MRI. Patients were followed for RA development ≤ 1 year, defined as fulfilling the classification criteria or initiation of disease-modifying antirheumatic drugs because of the expert opinion of RA. The added predictive value of foot MRI to hand MRI was evaluated. Results Fifty-two percent developed RA. Foot tenosynovitis was predictive (OR 2.55, 95% CI 1.01–6.43), independent of BME and synovitis (OR 3.29, 95% CI 1.03–10.53), but not independent of CRP and number of swollen joints (OR 2.14, 95% CI 0.77–5.95). Hand tenosynovitis was also predictive independent of BME and synovitis (OR 3.99, 95% CI 1.64–9.69) and independent of CRP and swollen joints (OR 2.36, 95% CI 1.04–5.38). Adding foot tenosynovitis to hand tenosynovitis changed the sensitivity from 72 to 73%, specificity from 59 to 54% and AUC from 0.66 to 0.64; the net reclassification index was − 3.5. Conclusion MRI-detected tenosynovitis of the foot predicts progression to RA. However, adding MRI of the foot does not improve the predictive accuracy compared to MRI of the hand alone. In view of cost reduction, the performance of foot MRI for prognostic purposes in UA can be omitted.